Sistematización de la construcción del personaje Goyo Yic en la obra “Flor de Amate”, 2022-1 (2024)
This project is based on the process of creating the character Goyo Yic in the play “Flor de Amate”, which was experienced by the student Anderson Andrés Espejo Murillo in the course of Theater and Convivio of the Bachelor of Performing Arts. Mainly, it investigates the experience lived by the actor Anderson Espejo during the classes, and the didactic strategies that the teacher Yuly Valero used, in the course Theater and Convivio, to develop the character. During the project, the four keys of the festive actor that Misael Torres proposes to us, which served to prepare the actor during the scene, are explored. This research is carried out through the steps that Oscar Jara proposes to us to carry out the systematization of experiences. Ultimately, this project seeks to provide a methodological route for the creation of characters to future master artists.